Irritation Test of Cream Preparations Made from Purple Cabbage Extract Against Healthy Skin Using The Path Test Method - Deswani Deswani; Sri Djuwitaningsih; Harpolia Cartika; Paul Malau (JURNAL INFO KESEHATAN, 2025)
Testing for skin irritation caused by new substances is a critical component of safety evaluation procedures. Pharmaceutical formulations and active ingredients intended for topical application have the potential to cause skin irritation, necessitating thorough safety assessments prior to public distribution. This study aimed to evaluate the primary irritation potential of a purple cabbage extract cream using the patch test method on healthy older adults. The experimental research involved 18 volunteers, who were administered 0.625% purple cabbage extract cream and a placebo preparation without the test substance. The test materials were applied twice daily over a period of 72 hours. Observations were conducted at baseline (0 hours) and at 24, 48, and 72 hours post-application. The degree of skin irritation was then calculated based on the recorded data. The results indicated a primary irritation index of 0.1, suggesting that the purple cabbage extract cream did not cause skin irritation. It can be concluded that the purple cabbage extract cream is safe for skin application in the tested population. Future research should explore the effects of purple cabbage cream on different skin locations, as skin sensitivity can vary across different areas of the body.